Does registered nurse involvement in improving healthcare services, influence registered nurse retention?. (September 2022) - Robinson, Jane; Engward, Hilary; Godier-McBard, Lauren; Jones, Kerry
Background: Registered nurses are 'critical' to population health, international responses to emergencies, epidemics and disasters. Retention of registered nurses (RNs) is an international nursing priority. In England, RNs are encouraged to be involved in improving healthcare services. This benefits quality of care, operational and financial performance. However, RN involvement in improvement may reduce RN retention. It is important to understand this relationship when developing effective RN retention strategies. Aim: The purpose of this research is to describe possible relationships between RN involvement in improving healthcare services and RN retention, using published 2018 data for National Health Service (NHS) Trusts in England. Methods: The relationship between RN involvement in improving healthcare services and RN retention was explored using a correlational design, involving secondary data from the annual NHS Staff Survey and Model Hospital. Results: In mental health NHS Trusts in England, a statistically significant, positive correlation of 0.24 was found between RN 'ab(ility) to make suggestions for improvement' and RN retention. In mental health NHS Trusts, a statistically significant correlation of 0.278 was found between RNs 'making improvements happen' and RN retention. In acute NHS Trusts in England, a statistically significant, negative correlation of −0.15 was identified between RNs 'mak(ing) improvements happen' and RN retention. Conclusions: The findings suggest that RN retention factors in mental health and acute NHS Trusts differ from community and specialist NHS Trusts in England. This is an important consideration for national RN retention programmes as a single approach to RN retention may not be effective across all healthcare settings.